2019
DOI: 10.21161/mjm.180230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathogenic bacteria on the salted fish Lutjanus vivanus in Sorong City of West Papua

Abstract: Aims: Fisheries-based food is needed by humans as a protein source, one of which is salted fish Lutjanus vivanus. Market demand for this product in Indonesia is quite high. The aim of the study was to identify pathogenic bacteria in salted fish L. vivanus. Methodology and results: The method used in this study was descriptive method including pathogenic test, bacterial genomic DNA isolation based on 16 sRNA gene using prokaryotic specific primers, namely 63f forward primer (5′-CAG GCC TAA CAC ATG CAA GTC-3′) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
1
0
0
1
Order By: Relevance
“…However, another same bacterial strain found in our research is B. altitudinis. A study shows that B. altitudinis A-19 16S strain gives partial hemolytic activity in salted fish L. vivanus in Indonesia [22]. In our study, it showed total beta hemolysis and hence a suggested potential pathogen.…”
Section: Discussionsupporting
confidence: 58%
“…However, another same bacterial strain found in our research is B. altitudinis. A study shows that B. altitudinis A-19 16S strain gives partial hemolytic activity in salted fish L. vivanus in Indonesia [22]. In our study, it showed total beta hemolysis and hence a suggested potential pathogen.…”
Section: Discussionsupporting
confidence: 58%
“…Dengan kandungan air yang cukup tinggi maka ikan merupakan media yang cocok untuk kehidupan bakteri pembusuk atau mikroorganisme lain. Adanya mikroba tersebut menyebabkann ikan sangat cepat mengalami proses pembusukan (Hardianti et al, 2019). Selain dari kandungan air yang cukup tinggi pada ikan, suhu dan kelembaban udara serta lingkungan yang tidak dapat mempercepat proses pembusukan.…”
Section: Pendahuluanunclassified